Produkty tradycyjne szansą na konkurencyjnym rynku UE - Rak, Lech (Traditional Products - Chance on Competitive Market of the European Union, 2007)
In this paper the traditional food are shown as products which support image creation of local rural regions. The European Union enabled protection of traditional registered food products classified into three groups as follows: Protected Designation of Origin, Protected Geographical Indication and Traditionally Specialty Guaranteed. Food products should be registered on national and next European Union level. The protection at the Union level allows marking goods with special symbols, which helps consumers to recognize products and their place of origin. It also fullfills modern consumers' expectation for food which represents special exceptional features: smell, taste, traditional methods of production, and unique values of quality. Registration procedure needs to join efforts of local society inachieving common aim - promoting product as well as own tradition, culture, and social environment. Activities focused on registration process create new initiatives especially in agrotourism what creates new workplaces. It improves quality level of life of local societies. Up to now 231 traditional food products are already registered in Poland. From this group 17 items are under registration procedure on Union level. None of the registration processes of Polish traditional food products heve been computed yet.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 156-166